A New Subblock Segmentation Scheme in Partial Transmit Sequence for Reducing PAPR Value in OFDM Systems - jawhar, yasir amer; Ramli, Khairun Nidzam; Taher, Montadar Abas; Shah, Nor Shahida Mohammed; Audah, Lukman Hanif; Ahmed, Mustafa Sami (International Journal of Integrated Engineering, 2018)
Partial transmit sequence (PTS) is considered an efficient algorithm to alleviate the high peak-to-average power ratio (PAPR) in orthogonal frequency division multiplexing (OFDM) systems. The PTS technique is depended on the partitioning the input data sequence into the several subblocks, and then weighting these subblocks with a group of the phase factors. There are three common types of partitioning schemes: interleaving scheme (IL-PTS), adjacent scheme (Ad-PTS), and pseudo-random scheme (PR-PTS). The three conventional partitioning schemes have various performances of the PAPR value and the computational complexity pattern which are considered the main problems of the OFDM system. In this paper, the three ordinary partition schemes are analyzed and discussed depending on the capability of reducing the PAPR value and the computational complexity. Furthermore, new partitioning scheme is introduced in order to improve the PAPR reduction performance. The simulation results indicated that the PR-PTS scheme could achieve the superiority in PAPR mitigation compared with the rest of the schemes at the expense of increasing the computational complexity. Furthermore, the new segmentation scheme improved the PAPR reduction performance better than that the Ad-PTS and IL-PTS schemes.